2017
DOI: 10.5327/z2594539420170000175
|View full text |Cite
|
Sign up to set email alerts
|

Use of 125iodine seeds (ROLLIS) for intra-operative localization of nonpalpable breast lesions: analysis of the implant of 338 seeds in 284 patients

Abstract: To analyze the feasibility, efficacy and results of the use of 125Iodine seeds for intra-operative localization of nonpalpable breast lesions. Method: Retrospective review of 284 patients, referred by various breast specialist surgeons, with radiologically detected but clinically nonpalpable microcalcifications or nodules, submitted to pre-operatory 125Iodine seed implant, between July 2012 and September 2016. A total of 338 seeds were implanted in ordinary radiologic departments, supported by ultrasonography … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Several other studies have looked at the differences in terms of other outcomes between the two techniques. Most have reported favourable outcomes for ROLLIS in terms of reduced excision margins required, reduced re‐excision rates and better cosmetic outcomes 6,11,12 With the introduction of ROLLIS, some centres have also reported more efficient utilization of radiology resources. Sharek et al 2 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several other studies have looked at the differences in terms of other outcomes between the two techniques. Most have reported favourable outcomes for ROLLIS in terms of reduced excision margins required, reduced re‐excision rates and better cosmetic outcomes 6,11,12 With the introduction of ROLLIS, some centres have also reported more efficient utilization of radiology resources. Sharek et al 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Several other studies have looked at the differences in terms of other outcomes between the two techniques. Most have reported favourable outcomes for ROLLIS in terms of reduced excision margins required, reduced re-excision rates and better cosmetic outcomes 6,11,12 With the introduction of ROLLIS, some centres have also reported more efficient utilization of radiology resources. Sharek et al 2 reported that patients had reduced wait times for percutaneous breast biopsies by 3.4 days (45% improvement) as the seeds can be placed in any interventional appointment, thus freeing up timeslots which would have been allocated to hook-wire placements.…”
Section: Discussionmentioning
confidence: 99%
“…The ROLL technique consists of the use of a radiotracer, where about 0.2 to 0.5 mL of 99m-technetium-labeled colloidal albumin ( 99m Tc-MAA) is injected directly into the breast [9], under ultrasound or stereotactic mammography guidance. As technetium is a gamma-type radiation emitter [11], a gamma detector device is needed to identify the marker during surgery [12]. It is possible to perform ROLL in conjunction with sentinel lymph node biopsy (SLNB) using the same radioactive tracer.…”
Section: Introductionmentioning
confidence: 99%
“…After the procedure, mammography is performed to confirm the seed location [14]. The use of a gamma detector device, such as a gamma probe, is necessary during surgery to identify the seed location [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation